Functional characterization of PaLAX1, a putative auxin permease, in heterologous plant systems - Hoyerová, Klára; Perry, Lucie; Hand, Paul; Lanková, Martina; Kocábek, Tomás; May, Sean; Kottová, Jana; Paces, Jan; Napier, Richard; Zazímalová, Eva (Plant physiology, 2008)
We have isolated the cDNA of the gene PaLAX1 from a wild cherry tree (Prunus avium). The gene and its product are highly similar in sequences to both the cDNAs and the corresponding protein products of AUX/LAX-type genes, coding for putative auxin influx carriers. We have prepared and characterized transformed Nicotiana tabacum and Arabidopsis thaliana plants carrying the gene PaLAX1. We have proved that constitutive overexpression of PaLAX1 is accompanied by changes in the content and distribution of free indole-3-acetic acid, the major endogenous auxin. The increase in free indole-3-acetic acid content in transgenic plants resulted in various phenotype changes, typical for the auxin-overproducing plants. The uptake of synthetic auxin, 2,4-dichlorophenoxyacetic acid, was 3 times higher in transgenic lines compared to the wild-type lines and the treatment with the auxin uptake inhibitor 1-naphthoxyacetic acid reverted the changes caused by the expression of PaLAX1. Moreover, the agravitropic response could be restored by expression of PaLAX1 in the mutant aux1 plants, which are deficient in auxin influx carrier activity. Based on our data, we have concluded that the product of the gene PaLAX1 promotes the uptake of auxin into cells, and, as a putative auxin influx carrier, it affects the content and distribution of free endogenous auxin in transgenic plants.
Keywords: gravitropismus; listy rostlin; exprese genu; Gene Expression; fenotyp; Phenotype; slivoň; Arabidopsis; fylogeneze; Phylogeny; kvetoucí vrcholky rostlin; komplementární DNA; membránové transportní proteiny; molekulární sekvence - údaje; Amino Acid Sequence; kyseliny indoloctové; Flowering Tops; 2,4-Dichlorophenoxyacetic Acid; Gravitropism; Prunus; Membrane Transport Proteins; Plants, Genetically Modified; Nicotiana; Indoleacetic Acids; Genetic Complementation Test; Plant Leaves; testy genetické komplementace; sekvence aminokyselin; geneticky modifikované rostliny; kyselina 2,4-dichlorfenoxyoctová; Molecular Sequence Data; DNA, Complementary; tabák